Identifikasi Sakarin pada Es Kelapa Muda yang Dijual di Pasar Rajawali Kota Palangka Raya: Identification of Saccharin in Coconut Beverage from Rajawali Market in Palangka Raya - Pratomo, Guntur Satrio (Jurnal Surya Medika (JSM), 2021)
Saccharin is a class of food additives permitted by Indonesia Republic Minister of Health Regulation No. 33 of 2012 for use in drinks, but if consumed in excess can cause harmful effects on health such as causing allergies and bladder cancer. The purpose of this study was to determine the presence of saccharin in coconut ice drinks in Pasar Rajawali Kota Palangka Raya. The sample used was 5 samples and the sampling technique was saturated sampling. Saccharin examination is done qualitatively using the resorcinol method. The results of research that has been done show that all samples of coconut ice drinks that have been tested negatively contain saccharin sweeteners.